PENGARUH VARIASI METODE DRILL DALAM MENINGKATAN KETERAMPILAN SHOOTING BOLA BASKET EKSTRAKULIKULER SMPN 2 CIASEM - Mursyidan, Ali; Iqbal, Rahmat; Fauzi Dermawan, Dikdik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of drill method variations on improving basketball shooting skills among extracurricular students at SMPN 2 Ciasem. The research employed an experimental method using a pre-test and post-test design. The sample consisted of 12 male students who were core players of the basketball team. The instrument used was a basketball shooting test adapted from the AAHPERD Basketball Skills Tests. The treatment was conducted over eight sessions within two weeks. Data analysis included normality testing, homogeneity testing, and paired sample t-test. The results showed that the mean pre-test score was 3.33, which increased to 5.58 in the post-test. The t-test results indicated a significance value of p < 0.05, meaning there was a significant difference between pre-test and post-test scores. Based on these findings, it can be concluded that variations of the drill method have a significant effect on improving basketball shooting skills. This method can be used as an effective learning approach to enhance shooting skills among junior high school students.